Biofuels and food security: Balancing needs for food, feed, and fuel - International Food Policy Research Institute (International Food Policy Research Institute, 2008)
Biofuel demand is increasing because of a combination of growing energy needs; rising oil costs; the pursuit of clean, renewable sources of energy; and the desire to boost farm incomes in developed countries. In turn, the need for crops-such as maize and sugarcane-to be used as feedstocks for biofuels has increased dramatically. That demand has had a significant and increasing impact on global food systems. The effects of growing biofuel demand are interwoven with tightening grain markets, which reflect demographic shifts and improved diets. In developing countries, as populations grow and incomes rise, diet preferences are shifting from staple crops to higher-value products like meat and dairy. As a result, the demand for grain- and protein-based animal feed is soaring and competing with food needs. These changes have led to increasing pressures on global agricultural markets and higher food costs. Poor people in both rural and urban areas are disproportionately vulnerable to these forces because they spend a large share of their incomes on food. Biofuels subsidies in developed countries tend to drive up food prices, thus reducing consumption and nutritional well-being for net buyers. The higher prices for commodities resulting from biofuel feedstock production can mean higher incomes for some farmers in developing countries and better agricultural wages for laborers, although the question of distribution among winners and losers remains. Another outcome for developing countries could be increased pressure on fragile natural resources on which poor farmers depend, potentially further degrading land and stressing limited water supplies. Over the coming decades, global food and agricultural systems not only will continue to come under the strain of providing for the competing needs of food, feed, and fuel, but will also face greater pressure from climatic and other economic changes. Urgent research is needed now to address these trends and protect the livelihoods of poor people. IFPRI uses innovative quantitative and analytical techniques to help policymakers and international institutions assess the potential benefits and risks of biofuels and explore ways to provide income-generating opportunities for the world's farmers while minimizing resource degradation and food insecurity. Critical questions include how global food systems can meet growing food, feed, and fuel needs while contributing to the reduction of poverty and hunger.